Tinjauan Unsur-Unsur Pengendalian Intern Sistem Akuntansi Pengeluaran Kas pada Koperasi Wanita Petra Palembang - Septiani Fransisca; Muhammad Akbar Anugrah (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
This study aimed to review the elements of intern control on Koperasi Wanita Petra Palembang. The data used in the form of interviews with related sections. The data was primary, because the researchers designed the flow chart of accounting system of cash expenditure based on the result of the interview obtained. But researchers were also supported by other secondary data. The results showed that the accounting system of cash expenditure on Koperasi Wanita Petra Palembang was quite good. However the achievement showed 53% fulfilled as the elements of intern control of accounting system cash expenditure. The remaining 47% has not been fulfilled as the intern controlling elements of the accounting system cash expenditure. A review was performed on several control items such as organization, authorization system and recording procedures as well as healthy practices.